Evaluation on an internal surface crack in a compound tube - Ali A.A.; Purbolaksono J.; Khinani A.; Rashid A.Z.; Tarlochan F. (2023)
In this paper stress intensity factors of a longitudinal semiellipti-cal surface crack on the inner surface in a compound tube subjected to internal pressure are presented. Variations of modulus of elasticity and thickness for the inner part of the tube are used in order to evaluate their effects on the normalized stress intensity factors. The boundary element method is used to analyze the problems. The increasing of thickness of the inner region causes decreasing values of the normalized stress intensity factor, as the modulus of elasticity for the inner part is greater than that of the outer part. Conversely, if the modulus of elasticity for the inner region is smaller, the increasing of thickness of the inner part would give increasing values of the normalized stress intensity factor. A larger inner radius and smaller thickness of the tube gives a higher normalized stress intensity factor. 2009 by ASME.